An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.

Synergistic combination of ZnCl2/Cu-BTC MOF for the photocatalytic oxidative deamination of benzylamines using CO2 under visible-light irradiation - Kumar, Amod; Bhatt, Sakshi; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Jain, Suman L. (ACS Applied Engineering Materials, 2024)
This paper demonstrates the first CO2-mediated oxidative deamination of benzylamines to benzaldehydes using a combination of ZnCl2 and Cu-BTC MOF as photocatalysts in a carbon tetrachloride solvent under visible-light irradiation. Interestingly, the synergistic combination of ZnCl2 and Cu-BTC afforded the targeted oxidation of benzylamine to benzaldehyde, wherein CO2 acted as an oxidant. The individual components yielded the corresponding imine as the main product, resulting from the oxidative coupling of the benzylamine. DFT calculations and computational studies supported the proposed reaction pathways involving the formation of an intermediate imine from benzylamine via dehydrogenation followed by hydrolysis to produce benzaldehyde. This work, demonstrating the use of CO2 as an oxidant, may open up new avenues for CO2 utilization in chemical production by using sustainable light energy.